2001
DOI: 10.1161/hh2401.101755
|View full text |Cite
|
Sign up to set email alerts
|

Increased Ischemia-Induced Angiogenesis in the Staggerer Mouse, a Mutant of the Nuclear Receptor Rorα

Abstract: Ror alpha is an orphan nuclear receptor. In homozygous staggerer mutant mice (Ror alpha(sg/sg)), a deletion within the Ror alpha gene leads to an overexpression of inflammatory cytokines. Because inflammation and hypoxia are 2 key stimuli of ischemia-induced angiogenesis, we studied the role of Ror alpha in this setting. Ischemia was induced by ligation of the right femoral artery in C57BL/6 Ror alpha(+/+) and Ror alpha(sg/sg) mice. After 3 and 28 days, angiogenesis was evaluated by microangiography, measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…However, increased postischemic angiogenesis was observed in the hindlimbs of homozygous staggerer mice, which may suggest ROR␣ as a negative regulator of ischemia-induced angiogenesis. 17 One of the potential explanations of this discrepancy could be differential roles of functional domains of ROR␣ in new vessel formation. We observed here that DBD of ROR␣ was sufficient to induce protein stability as well as transcriptional activation of HIF-1 (supplemental Figure IV).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, increased postischemic angiogenesis was observed in the hindlimbs of homozygous staggerer mice, which may suggest ROR␣ as a negative regulator of ischemia-induced angiogenesis. 17 One of the potential explanations of this discrepancy could be differential roles of functional domains of ROR␣ in new vessel formation. We observed here that DBD of ROR␣ was sufficient to induce protein stability as well as transcriptional activation of HIF-1 (supplemental Figure IV).…”
Section: Discussionmentioning
confidence: 99%
“…15,16 In the staggerer mice, angiogenesis is enhanced markedly after ischemia induced by the ligation of the femoral artery. 17 In the vascular system, ROR␣ mRNAs have been detected in human smooth muscle cells (SMCs), endothelial cells (ECs), as well as mammary arteries. 16,18 ROR␣ expression level is significantly decreased in human atherosclerotic plaques, whereas increased expression is observed after treatment with interleukin (IL) 1␤, tumor necrosis factor (TNF) ␣, and lipopolysaccharide (LPS) in both ECs and human aortic SMCs.…”
mentioning
confidence: 99%
“…6 Femoral artery ligation induces a rapid and transient increase in ROR␣ mRNA in ischemic tissue. In Rora sg/sg mice, angiogenesis is markedly enhanced after ischemia induced by ligation of the femoral artery: capillary density is increased in the ischemic hindlimb, and leg perfusion is improved.…”
Section: Ror␣ and Ischemia-induced Angiogenesismentioning
confidence: 99%
“…In addition, ROR␣ activates the apolipoprotein A-I (apoA-I) and apoC-III gene transcription, 3,4 modulates the vasomotor tone of small resistance arteries, and participates in the regulation of postischemic angiogenesis. 5,6 This review focuses on the link between ROR␣, vascular biology, and cholesterol homeostasis. Interestingly, recent findings suggest that ROR␣ is an intracellular cholesterol target.…”
mentioning
confidence: 99%
“…In line with these findings, Mamontova et al (20) reported that staggerer mice, which carry a deletion within ROR␣ gene that prevents the translation of the LBD, develop severe atherosclerosis in response to a high fat diet. Recently, ROR␣ has been shown to be a negative regulator of ischemiainduced angiogenesis (21) and a possible factor in bone metabolism (22). Finally, ROR␣ has been found to be highly expressed in skeletal muscle (5) and to be involved in myogenesis (23).…”
mentioning
confidence: 99%